An analysis of the perceived service quality of hospitality industry in Rio de Janeiro through the SERVQUAL model: a multiple case study - Bastos, Ana Rita dos Santos (2016)
Brazil is under political and financial crises where the end seems far away. Because of that, researchers argue that the hotel rooms offered by Rio de Janeiro, built to host the Olympic Games 2016, will be difficult to occupy after the event. It is then necessary for the hotels to understand how guests perceive the service quality in order to adapt to this new era. If guests’ perceptions meet or exceed their expectations, they will be satisfied and will probably return. Thus based on the SERVQUAL approach, this paper aims to study the impact of the service dimensions on the guests’ overall satisfaction at hotels of Rio de Janeiro. Two hotels were considered representative of the city in terms of service quality and customers’ profile. Interviews to the hotel managers were performed, and questionnaires to the guests were administered. Among the five SERVQUAL dimensions – Reliability, Tangibles, Responsiveness, Assurance, and Empathy – the Empathy dimension appears to be the only one that affects the guests’ overall satisfaction. The study could also identify that gender, country of residence, home country and family income have an impact on guests’ satisfaction. This study has no intention of generalization, but rather of refining the theory about services and the SERVQUAL model.